DIFFERING EFFECTS OF CONFERENCE AND PEER ASSESSMENT ON WRITING SKILL OF EFL LEARNERS - Anvar, Maryam Manafi; Nemati, Azadeh (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This study intended to demonstrate the significant differences between conference and peer evaluation on writing skill of EFL learners in Pooyesh Language House of Bandar Lengeh. To find out the differences, two types of tests (pre- test before treatment and receiving feedback, post- test after treatment and receiving feedback) were given to two groups of students (30 students for conference and 30 students for peer evaluation). The participants were all teen and adult students who were studying at the same level in this Language House. The writing tests were taken from their previous books which they had practiced before. The pre-test was given to students. In conference group, a mark was given to them by their teacher and during the term the students learned how to write through their teachers comments, but in peer evaluation group, through their classmates comments, so in the second group the classmates just checked each others papers and found errors without giving any mark, because they were not familiar with assessment system; it was the teacher task. In the first group, the teacher was familiar with assessment system, but in peer evaluation group the students found how to check other students’ writing as treatment, according to IELTS writing assessment criteria, through their teacher guidance. The post- test was given at the end of the term and previous method was repeated. The results of the study indicated that there was no statistically significant difference between conference and peer evaluation, so the research questions were rejected. The results gained from the two variables were analyzed according to quasi experimental design.